Advances in Plasma Processes for Polymers II - Park, Choon-Sang (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue aimed to compile original and cutting-edge research works in the fields of plasma process, polymerization, synthesis, characterization, treatment, modification, manufacturing, and applications of functional plasma-processed polymers.